Utilizing item response theory for the analysis of self-regulated learning scale in mathematics - Dewanti, Sintha Sih; Jasmine Nurul Izzah; Shinta Puspa Kiranasari; Kholifatul Fatoni Sholihin (Jurnal Elemen, 2024)
In the learning process, students must be able to regulate themselves. This is an effort to improve the quality of student learning, especially their learning achievement. The purpose of this study is to empirically analyze the characteristics of self-regulation skills in learning mathematics. The analysis was carried out by utilizing Item Response Theory (IRT) with a Partial Credit Model (PCM). This study is a descriptive quantitative study with the subjects of the study being 123 students of grade 10 of Senior High Schools in Yogyakarta. Data collection was carried out using a questionnaire that had been developed and its item characteristics were analyzed using IRT. The independent learning scale questionnaire in mathematics consists of 16 statement items and measures 5 aspects. Based on all the questions that are feasible to be analyzed using the PCM model, it is known that there are 5 aspects that fit, namely (1) self-confidence, (2) discipline in learning, (3) active in learning, (4) responsibility, and (5) motivation in learning. This instrument can be used to measure students' self-regulation skills in learning mathematics based on their ability level.